The Revitalization of Blue-and-White Decoration Education in Jingdezhen Colleges and Universities: Incorporation of a New Flowing-Color Landscape Process - Chunlei, Zhao; Krutasaen, Watanapun (Journal of Roi Kaensarn Academi, 2024)
Jingdezhen's higher education institutions have always regarded the blue-and-white decoration course as essential to ceramic decoration art education. However, the traditional blue-and-white craftsmanship is challenging to master, students' enthusiasm for learning is not high, and the quality of student work varies. Therefore, this study aims to assess the integration of Jingdezhen's new flowing-color landscape craftsmanship into higher education to improve the quality of students' assignments and interest in learning. The research objectives include: 1) exploring the reasons for students' lack of enthusiasm in higher education blue-and-white teaching; 2) incorporating the new flowing-color landscape craftsmanship into the higher education blue-and-white course and achieving teaching results; 3) Comparing results, questionnaire surveys, and student feedback. The study adopts a mixed research method. This research uses a mixed research method, covering interviews with 21 students and four teachers, classification evaluation of 468 student works, grade comparison, and a questionnaire survey comparing the difficulty of blue-and-white decoration craftsmanship, students' satisfaction with their works, and interest in learning. Additionally, it includes student feedback. The research sample comprises 104 participants, including students from Jingdezhen Ceramic University's School of Science and Art, ceramic art enthusiasts, and industry experts. The research results show: 1) The complexity and difficulty of traditional blue-and-white decoration techniques have always been significant obstacles for students, many of whom cannot master them, leading to a decline in the quality of blue-and-white decoration assignments and reducing enthusiasm for learning. 2) Incorporating the new flowing-color landscape technique into blue-and-white decoration has increased students' interest and significantly improved project results. 3) The comparison of questionnaire survey results and student feedback indicates that this novel process has achieved good results in the higher education environment. Integrating Jingdezhen's flowing color landscape into the higher education blue-and-white course revitalized higher education. It promoted the development of the new blue-and-white ceramic flowing-color landscape decoration craftsmanship.